Influence of wrist position on maximum grip force in a post-operative orthosis. (February 2017) - Burssens, Arne; Schelpe, Nathalie; Vanhaecke, Jeroen; Dezillie, Marleen; Stockmans, Filip
Background: Flexor tendon repair in the hand remains challenging in avoiding tendon rupture and adhesion formation. Post-operative mobilization has been shown to be critical in regaining functional range of motion. Objectives: The objective of this study is 2-fold: to assess the influence of wrist position on maximum grip force generated in a post-operative orthosis and to determine the correlation between this maximum grip force and an individual's grip strength. Study design: Clinical measurement Methods: A total of 30 uninjured wrists of right-handed men were given a post-operative orthosis with an incorporated Caroli-hinge. The maximum grip force was measured according to a different wrist position ranging from −30° extension until 80° of flexion using a 10° interval. These measurements were plotted out on a graph for regression analysis. A correlation was determined between measurements in a neutral wrist position and maximum grip strength generated without an orthosis. To assess the coherence of the measurements, a mean intraclass correlation coefficient was used. Results: The maximum grip force values were statistically significantly different in every wrist position and decreased progressively with an increasing flexion angle ( p  < 0.05). This relationship is expressed in a logistic regression curve f ( x ) = −4.98 + 16.92/(1 + (x/8.59)) 2.24 . A wrist position of 4.4° of flexion was derived from this function to cause a maximum grip force reduction of 33%. Further analysis showed a force decrease of 50% at 23.2° and 66% at 51.8° of wrist flexion. The grip strength measured without an orthosis showed a positive correlation with previous measurements (Spearman's correlation coefficient = 0.74 for the right hand and 0.72 for the left hand ( p  < 0.001)). Conclusions: The obtained logistic function allowed to derive the wrist position needed in a post-operative orthosis to obtain a desired amount of maximum grip force reduction. Clinical relevance: Measuring a high grip force in a clinical setting of flexor tendon repair on the contralateral non-affected hand could indicate the use of an increased flexion angle in a post-operative orthosis. This reduces the load transferred on the tendon repair when involuntary contractions take place, for example, during sleeping when positioned in a post-operative orthosis.